2016
DOI: 10.1021/acs.jpca.6b02929
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Two-Photon Absorption to Gerade Excited Singlet States of Diphenylacetylene and Diphenylbutadiyne Using Optical-Probing Photoacoustic Spectroscopy

Abstract: Simultaneous two-photon absorption to one-photon forbidden electronically excited states of diphenylacetylene (DPA) and diphenylbutadiyne (DPB) was investigated by means of highly sensitive optical-probing photoacoustic spectroscopy. The incident laser power dependencies on photoacoustic signal intensity indicate that the signals are dominated by the two-photon absorption regime. Two-photon absorption is responsible for transitions to gerade excited states based on the selection rule. The two-photon absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 73 publications
(141 reference statements)
2
16
0
1
Order By: Relevance
“…The experimental setup for OPPAS measurement has been described elsewhere. 17,18 An optical parametric oscillator (OPO) laser (Continuum, Panther EX OPO; linearly polarized, pulse width 3-5 ns, line width < 6 cm -1 ) pumped by third harmonic of a Nd 3+ :YAG laser (Continuum, Surelite Ⅱ; pulse width 4-6 ns, repetition rate 10 Hz) and a He-Ne laser (LASOS,…”
Section:  Experimentalmentioning
confidence: 99%
See 3 more Smart Citations
“…The experimental setup for OPPAS measurement has been described elsewhere. 17,18 An optical parametric oscillator (OPO) laser (Continuum, Panther EX OPO; linearly polarized, pulse width 3-5 ns, line width < 6 cm -1 ) pumped by third harmonic of a Nd 3+ :YAG laser (Continuum, Surelite Ⅱ; pulse width 4-6 ns, repetition rate 10 Hz) and a He-Ne laser (LASOS,…”
Section:  Experimentalmentioning
confidence: 99%
“…The experimental setup for OPPAS measurement has been described elsewhere. , An optical parametric oscillator (OPO) laser (Continuum, Panther EX OPO; linearly polarized, pulse width 3–5 ns, line width <6 cm –1 ) pumped by third harmonic of a Nd 3+ :YAG laser (Continuum, Surelite II; pulse width 4–6 ns, repetition rate 10 Hz) and a He–Ne laser (LASOS, LGK 7634; ≥2 mW, cw 632.8 nm) were used as the excitation and probe sources, respectively. The excitation laser power was attenuated with a variable neutral density filter to obtain the incident laser power dependence on the OPPAS signal.…”
Section: Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4 Additionally, small-molecule organic light-emitting diodes (OLEDs) have attracted enormous attention because of their low-cost fabrication and production; they are applicable to a wide range of display devices, such as flat-panel displays and flexible displays. 5 Tolanes, which have a structure of two aromatic rings connected by alkyne moieties, have been recognized as promising candidates for small-molecule fluorophores owing to their broad applications as two-photon absorbers, 6 liquid crystals, 7 and organic semiconductors. 8 However, it has been reported that tolanes are not emissive at room temperature because the excitons generated after excitation immediately undergo internal conversion from fluorescent pp* to dark ps* excited states with a trans-bend molecular shape.…”
Section: Introductionmentioning
confidence: 99%